Occupational injury risk among ambulance officers and paramedics compared with other healthcare workers in Victoria, Australia: analysis of workers' compensation claims from 2003 to 2012. Issue 7 (16th March 2015) - Roberts, Minainyo Helen; Sim, Malcolm Ross; Black, Ollie; Smith, Peter
Abstract : Objective: To investigate occupational risk of musculoskeletal (MSK) and mental injury among ambulance officers and paramedics, and compare with nurse professionals, social and welfare professionals, and carers and aides in Victoria, Australia, using workers' compensation (WC) claims statistics. Methods: Data were retrieved from the Victorian Compensation Research Database (CRD). Analysis was restricted to claims received between 1 July 2003 and 30 June 2012. WC claim rates were calculated using labour force statistics, and expressed per 1000 full-time equivalent workers. Adjusted HRs with 95% CIs for injury risk were estimated using multivariable regression modelling. Results: Ambulance officers and paramedics had an upward trend in WC claim rates for all injuries and the highest rates for MSK and mental injury, in comparison with other healthcare workers during the study period. In the 2009–2012 time period, ambulance officers and paramedics' risk of lower back MSK and mental injury was approximately 13 times higher than nurse professionals, HRs 57.6 vs 4.4 and 17.77 vs 1.29, respectively. Social and welfare professionals had the second highest risk of mental injury, which was up to threefold greater than in nurses. Carers and aides and nurse professionals had similar HRs overall for all injury categories. Conclusions: Differential patterns of MSK and mental injury exist among healthcare occupational groups in Victoria, Australia. Given the significant findings, especially the high risks among ambulance personnel, future research should focus on the circumstances of injury to improve understanding and inform prevention programmes.